Computer applications in civil engineering - Regional Conference on Computer Applications in Civil Engineering (3rd : 1994 : Kuala Lumpur); Nasly Mohamed Ali; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Awam (Sekudai : UTM, 1995)
06